-(x+8)=12+2x

Simple and best practice solution for -(x+8)=12+2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+8)=12+2x equation:


Simplifying
-1(x + 8) = 12 + 2x

Reorder the terms:
-1(8 + x) = 12 + 2x
(8 * -1 + x * -1) = 12 + 2x
(-8 + -1x) = 12 + 2x

Solving
-8 + -1x = 12 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-8 + -1x + -2x = 12 + 2x + -2x

Combine like terms: -1x + -2x = -3x
-8 + -3x = 12 + 2x + -2x

Combine like terms: 2x + -2x = 0
-8 + -3x = 12 + 0
-8 + -3x = 12

Add '8' to each side of the equation.
-8 + 8 + -3x = 12 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = 12 + 8
-3x = 12 + 8

Combine like terms: 12 + 8 = 20
-3x = 20

Divide each side by '-3'.
x = -6.666666667

Simplifying
x = -6.666666667

See similar equations:

| F(x)=-9(-4)+5 | | 5x^2-90x=-400 | | 3x+12=5x-48 | | 7y-4=12y+21 | | -8q-7=-6q+15 | | c*2=-5 | | 4(x+4)+6=26 | | 12y-3(y-3)=6y+8-1(y+2) | | f(1)=10 | | y=5+-13 | | (9m+10).2= | | -7y+28=-3(5y+4) | | (x-(1+2i))(x-(1-2i))=0 | | 2y+3=9+6y | | 15x^2+5-[5(x^2-7)+9]= | | 5p^2=300+20p | | 2x-1+2x=4x+28 | | -6=-5 | | -31+6x=-1-3(-5x+1) | | 4k^3w+20k^2w^2+25kw^3=0 | | 4(6x^2-7)-[6(3x^2-4)+3]= | | 5n+3(n+a)=28 | | lx(x+8)+ln(x-1)=2lnx | | 7-2(4r+3)=-6 | | 3(4-x)=10+2x | | 2w^2-4w-70=0 | | 67-b=49 | | 4(7-2n)+4n=-5n+34 | | A=650-8(75) | | -3z^2+2z-35=0 | | y=0.5+4 | | -8c=24 |

Equations solver categories